2015
DOI: 10.1590/s1679-87592015088006303
|View full text |Cite
|
Sign up to set email alerts
|

Variation in cheliped form in two species of squat lobsters (Decapoda: Anomura) from Chile

Abstract: The current study describes the variation in cheliped form of two species of squat lobsters that inhabit the continental margin off Chile: Cervimunida johni and Pleuroncodes monodon. We compared their cheliped form in the context of the reproductive strategy. The general tendency of form variation of both species is similar: chelipeds change, on average, from longer and narrower pollex with short manus to a relatively shorter and wider pollex with longer manus from small to large individuals, respectively. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…showed significantly larger values than females. Similar male-biased dimorphism in cheliped dimensions was also reported in other decapod crustaceans, such as lobsters ( Claverie & Smith, 2010 ; Lezcano et al, 2015 ) and shrimps ( Mashiko, 1981 ; Mantel & Dudgeon, 2005 ). In Scylla , apart from body size dimensions, cheliped size is also postulated to play a significant role in female courting and settling a fight during mate guarding ( Waiho et al, 2015 ).…”
Section: Discussionsupporting
confidence: 78%
“…showed significantly larger values than females. Similar male-biased dimorphism in cheliped dimensions was also reported in other decapod crustaceans, such as lobsters ( Claverie & Smith, 2010 ; Lezcano et al, 2015 ) and shrimps ( Mashiko, 1981 ; Mantel & Dudgeon, 2005 ). In Scylla , apart from body size dimensions, cheliped size is also postulated to play a significant role in female courting and settling a fight during mate guarding ( Waiho et al, 2015 ).…”
Section: Discussionsupporting
confidence: 78%
“…Results suggest that the claws of male yeti crabs are larger and therefore under sexual selection, perhaps representing an advantage for reproduction (Andersson and Simmons, 2006;Jones and Ratterman, 2009;Shuker and Kvarnemo, 2021). Similar patterns of claw sexual dimorphism have been reported for species of Chrisostyloidea squat lobsters such as Uroptychus alcocki and Uroptychus scambus (Schnabel, 2009), and other deep-sea anomurans including Cervimunida johni (Lezcano et al, 2015), Munida intermedia (Mori et al, 2004), Munida iris (Williams and Brown, 1972), Munida microphtalma (Kassuga et al, 2008), Munida rugosa (Claverie and Smith, 2007;Claverie and Smith, 2010), Munidopsis erinacea (Tavares and Campinho, 1998), Munidopsis kaiyoae (Schnabel and Bruce, 2006), Munidopsis scobina (Creasey et al, 2000), Munidopsis sigsbei (Tavares and Campinho, 1998), Munidopsis papanui (Schnabel and Bruce, 2006), Pleuroncodes monodon (Lezcano et al, 2015), and Shinkaia crosnieri (Tsuchida et al, 2003). Although this is the first time that sexual dimorphism in weaponry is tested for yeti crabs in the family Kiwaidae, studies conducted on Kiwa tyleri from the Southern Ocean hydrothermal vent fields found that males have larger carapace length than females, and also reported that sexual dimorphism of the claw is apparent in this species, but this was not tested (Marsh et al, 2015;Thatje et al, 2015a).…”
Section: Discussionsupporting
confidence: 69%
“…For example, in two deep-water squat lobsters that exhibit precopulatory guarding, the guarding duration was shorter in P. monodon than in C. johni, and the authors proposed that these differences can be related to speciesspecific life-history traits such as mobility and intraspecific aggression, both expected to be higher in C. johni (Espinoza-Fuenzalida et al, 2012). Furthermore, the cheliped shape in these two species show a relation to the mating system and possibly to male aggressiveness, where C. johni large males have more arched chelipeds to inflict puncture wounds on opponents, while in P. monodon the chelipeds were straighter (Lezcano et al, 2015). In K. puravida, we found that males have larger claws that may be used as weaponry in male-male competition for access to females, and some antagonistic interactions have been observed (Thurber et al, 2011;Supplementary Material Video).…”
Section: Discussionmentioning
confidence: 99%
“…This state can be interpreted as a deviation from perfect symmetry on the part of an organism or a component of that organism ( Van Valen, 1962 ; Spani et al, 2020 ). In particular, many decapod crustaceans ( Lezcano et al, 2015 ; Hamasaki & Dan, 2022 ), including brachyurans, show asymmetry in the shape and size of their chela ( Scalici & Gherardi, 2008 ). The development of heterochely thus results from this disruption of bilateral symmetry ( Graham et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%